Proposed minimal diagnostic criteria for myelodysplastic syndromes (MDS) and potential pre-MDS conditions - Valent, Peter; Hofmann, Wolf-Karsten (OncoTarget, 2017)
Myelodysplastic syndromes (MDS) comprise a heterogeneous group of myeloid neoplasms characterized by peripheral cytopenia, dysplasia, and a variable clinical course with about 30% risk to transform to secondary acute myeloid leukemia (AML). In the past 15 years, diagnostic evaluations, prognostication, and treatment of MDS have improved substantially. However, with the discovery of molecular markers and advent of novel targeted therapies, new challenges have emerged in the complex field of MDS. For example, MDS-related molecular lesions may be detectable in healthy individuals and increase in prevalence with age. Other patients exhibit persistent cytopenia of unknown etiology without dysplasia. Although these conditions are potential pre-phases of MDS they may also transform into other bone marrow neoplasms. Recently identified molecular, cytogenetic, and flow-based parameters may add in the delineation and prognostication of these conditions. However, no generally accepted integrated classification and no related criteria are as yet available. In an attempt to address this challenge, an international consensus group discussed these issues in a working conference in July 2016. The outcomes of this conference are summarized in the present article which includes criteria and a proposal for the classification of pre-MDS conditions as well as updated minimal diagnostic criteria of MDS. Moreover, we propose diagnostic standards to delineate between ´normal´, pre-MDS, and MDS. These standards and criteria should facilitate diagnostic and prognostic evaluations in clinical studies as well as in clinical practice.
Gesehen am 08.10.2018